In-Service Transformer Oil Regeneration Based On Laboratory-Scale Process - Ab Ghani, Sharin; Sutan Chairul, Imran; Abu Bakar, Norazhar; Ahmad Khiar, Mohd Shahril; Zulkefli, Aminur Hazieq; Ahmad, Asimi Ana (Penerbit Akademia Baru, 2020)
This paper described in-laboratory oil regeneration process of aged transformer oil using adsorbent; Fuller’s earth. The niche of this paper is the usage of real aged transformer oil taken from an 11kV/433V in-service power transformer made by ACEC Transformer in 1986. The regeneration process is achieved by forcing a mixture of aged transformer oil and Fuller’s earth through a filter paper with the aid of a vacuum pump, hence producing reclaimed transformer oil. This oil was then inserted in an amber glass bottle, blanketed with nitrogen, tightly sealed, and labelled. To test the effectiveness of Fuller’s earth as adsorbent, parameters of Dissolved Decay Product (DDP) were measured using UV-Visible Spectrophotometer (UV-Vis) by referring to ASTM D6802. In addition, Total Acid Number (TAN) and Breakdown Voltage (BdV) measurement were carried out complying the ASTM D974 and ASTM D1816 respectively. Results of UV-Vis indicated that Fuller’s earth can adsorbed 25.24% of DDP in aged transformer oil. As the DDP decreased, TAN is 84.62% reduced while BdV increased 50%. These findings are parallel with the breakdown voltage mechanism due to acidity emergence. It is proved that Fuller’s earth is effective adsorbent for oil regeneration process.